Food of the world Philippines & Singapore - Workman, Wade; Puckett, Sidney (Chandni Chowk, Delhi Global Media, 2009)
The best food recipes from Philippines & Singapore
Intro -- Table of Contents -- The best food recipes from Philippines & -- Singapore.
Keywords: Cooking, Philippine; Cooking, Singaporean